Dynamics of scientific production on regionalization of higher education: A bibliometric study - Cuéllar Sánchez, Diana Mireya.; Dueñas Peña, Alex.; Núñez Valdés, Karen Patricia. (Kurdish Studies, 2024)
The regionalization of Higher Education goes beyond the mere expansion of academic programs to peripheral regions. It should involve a genuine recognition of the particularities and needs of each context, with educational programs that extend beyond the classroom and fill the gap in educational quality in these areas. The objective of this study is to address fundamental questions about international research on the regionalization of higher education. The analysis was based on specific criteria: documents published between 2013 and 2023, diverse document typologies, the English language, and presence in the SCOPUS database. Tools such as VOSviewer, Biblioshiny, and Excel were used to identify patterns and trends. The results reveal a total of 20 academic works, with the year 2016 standing out as the most active, representing 25% of the production. Despite fluctuations, no clear growth trend in production is perceived. Additionally, it is noted that the regionalization of education does not have a prominent presence in high-impact academic journals. This study emphasizes the need to intensify research in the field of regionalization of higher education, foster stronger collaboration among researchers, and raise the visibility of this topic in renowned journals. These steps are essential to effectively address the challenges associated with the regionalization of higher education and ensure that the specific needs of communities in all regions are met.
Keywords: Regionalización; Educación superior; Universidades